2020
DOI: 10.1108/pijpsm-04-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Organizational support and Chinese police officers’ attitudes toward intervention into domestic violence

Abstract: PurposeThe purpose of this paper is to examine Chinese police officers’ general support for police intervention into domestic violence, emphasizing adequate protection of the victims, and specific support for utilizing arrests to deal with the offenders.Design/methodology/approachThis study relies on survey data collected from 1,064 police officers who worked in multiple areas in two provinces of China between June and July of 2019. OLS models were used to test whether organizational variables are significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Therefore, officers who prioritize gender equality may perceive a protection order as a crucial means of support for victims, thereby increasing their willingness to assist in obtaining such orders. Our study aligns with previous literature that has identified the detrimental effects of DV tolerance and perceptions of gender equality on police attitudes and interventions in DV cases ( Lin et al, 2021 ; Sun et al, 2022 ; Wu et al, 2020 ). In conjunction with prior research, our findings underscore the importance of addressing officers’ tolerance for DV and their perceptions of gender equality to promote police service-oriented interventions in DV cases.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, officers who prioritize gender equality may perceive a protection order as a crucial means of support for victims, thereby increasing their willingness to assist in obtaining such orders. Our study aligns with previous literature that has identified the detrimental effects of DV tolerance and perceptions of gender equality on police attitudes and interventions in DV cases ( Lin et al, 2021 ; Sun et al, 2022 ; Wu et al, 2020 ). In conjunction with prior research, our findings underscore the importance of addressing officers’ tolerance for DV and their perceptions of gender equality to promote police service-oriented interventions in DV cases.…”
Section: Discussionsupporting
confidence: 90%
“…Supporting this idea, English (vs. American) officers tended to catch subtle forms of abuse (e.g., psychological) to a larger extent, given that much attention has been paid to non-violent warning signs (e.g., coercive control) in the UK (Robinson et al, 2016). Conversely, in China-where discretion is the arrest policy-, police officers were more reluctant to apply criminal punishment (Wu et al, 2020;Zhao et al, 2018). Particularly, when they faced minor physical injury and psychological abuse (Tam & Tang, 2005).…”
Section: Ipvaw Myths and Police Officers' Perceived Severity Of Ipvawmentioning
confidence: 99%
“…Lack of related training also contributes to unsatisfactory law enforcement performance (Li et al, 2021). Thus, education for police officers on domestic violence would not transmit critical ideas and knowledge to them without enough organizational support (Hayes et al, 2022; Wu et al, 2020). Furthermore, police officers are criticized for holding patriarchal beliefs (Liu, 2017; Zhang, 2005).…”
Section: Policing Domestic Violence In Chinamentioning
confidence: 99%